PENEGAKAN HUKUM TERHADAP PENGECER MINYAK GORENG OPLOSAN DI WILAYAH HUKUM POLSEK SENAPELAN - Pangestu, Aji Bagus; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Cooking oil is one of the basic human needs as a means of processing food ingredients. Cooking oil as a frying material is very important and its needs are increasing. Now the cooking oil crisis is almost evenly distributed in almost all cities in the country which is one of the world's biggest producers of palm oil. With the condition of cooking oil prices soaring increasingly high, making a number of business people sell oplosan cooking oil. Oplosan cooking oil is very dangerous for human health because it has been damaged.This research is a sociological or empirical research which is a type of research that uses the assumptions of the community in searching for facts that occur in the field to answer an existing problem. This research was conducted in the jurisdiction of the Riau High Prosecutor's Office. While the population and sample are parties related to the problem examined in this study, the source of the data used, primary data, secondary data, and tertiary data. Data collection techniques in this study were interviews and literature review.From the results of the research that the author did, it can be concluded, first, law enforcement against circulation of mixed cooking oil is still not running as it should, there are still problems in law enforcement namely one of them is the lack of personnel from the Drug and Food Control Agency so that there is still a lot of mixed cooking oil in circulation among the people. Second, the obstacles and efforts in overcoming the circulation of cooking oil include the lies in the law itself, where the law has not been effective in dealing with the rise of mix cooking oil in the market. In addition, the obstacle in overcoming the circulation of mixed cooking oil lies in the lack of a system of coordination between law enforcement officers and the Food and Drug Monitoring Agency in handling cases of circulation of cooking oil in the community.Keywords: Law Enforcement - Cooking Oil - Oplosan